What Drives the Performance of Selected MENA Banks? : A Meta-Frontier Analysis - Ben Naceur, Sami (IMF Working Papers; Working Paper ;, 2011)
This study examines the effect of financial-sector reform on bank performance in selected Middle Eastern and North African (MENA) countries in the period 1994 -2008. We evaluate bank efficiency in Egypt, Jordan, Morocco, Lebanon and Tunisia by means of Data Envelopment Analysis (DEA) and we employ a meta-frontier approach to calculate efficiency scores in a cross-country setting. We then employ a second-stage regression to investigate the impact of institutional, financial, and bank specific variables on bank efficiency. Overall, the analysis shows that, despite similarities in the process of financial reforms undertaken in the five MENA countries, the observed efficiency levels of banks vary substantially across markets, with Morocco consistently outperforming the rest of the region.Differences in technology seem to be crucial in explaining efficiency differences. To foster banking sector performance, policies should be aimed at giving banks incentives to improve their risk management and portfolio management techniques. Improvements in the legal system and in the regulatory and supervisory bodies would also help to reduce inefficiency.